2007
DOI: 10.1159/000101499
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effectiveness of Atypical Antipsychotics for the Treatment of Behavioural Problems in Persons with Dementia

Abstract: Background: To review published reports of the usage of atypical antipsychotics for behavioural problems of dementia patients. Methods: The electronic database Medline was searched from 1999 to 2006 with a combination of search terms including ‘behavioural problems’ and ‘atypical antipsychotics’. Results: Thirteen eligible studies were included in the overall analysis. The total number of participants was 1,683, of whom 1,015 received medication and 668 received placebo. Medications studied were risperidone, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 58 publications
0
39
0
1
Order By: Relevance
“…[17] Medications often result in adverse effects such as increased risk of mortality, excessive sedation, increased risk of falls, lethargy, and disorientation. [18][19][20][21][22] 1.3 Rationale for non-pharmacological approaches The use of psychotropic medications to reduce aggression overlooks the possibility that aggression may be related to environmental factors and may serve a communicative function for the PWD. For example, aggressive behaviors occur most frequently during ADLs such as bathing, dressing, and toileting, which naturally involve physical touch from a caregiver.…”
Section: Prevalence Of Aggression In Pwdsmentioning
confidence: 99%
“…[17] Medications often result in adverse effects such as increased risk of mortality, excessive sedation, increased risk of falls, lethargy, and disorientation. [18][19][20][21][22] 1.3 Rationale for non-pharmacological approaches The use of psychotropic medications to reduce aggression overlooks the possibility that aggression may be related to environmental factors and may serve a communicative function for the PWD. For example, aggressive behaviors occur most frequently during ADLs such as bathing, dressing, and toileting, which naturally involve physical touch from a caregiver.…”
Section: Prevalence Of Aggression In Pwdsmentioning
confidence: 99%
“…In the case of pharmacological interventions for behavioral disturbances, antipsychotic medications are typically used. However, in a meta-analysis of 13 studies, Yury and Fisher (2007) found that the use of atypical antipsychotic medication "is not very effective for the management of neuropsychiatric symptoms of dementia, and the effects are modest" (p. 216).…”
Section: Overview Of the Medical Modelmentioning
confidence: 99%
“…50 Apesar das evidências a favor do benefício do uso de antipsicóticos atípicos no tratamento de SCPD, obtidas a partir de estudos metodologicamente consistentes, duas metanálise recentes questionam os resultados dos estudos individuais. 51,52 Nestes trabalhos, o benefício do uso destas medicações no tratamento de SCPD foi de pequeno a moderado, e as drogas com maior evidência de eficácia terapêutica foram a risperidona e o aripiprazol. Demonstrou-se que a incidência de efeitos colaterais foi elevada, sendo um dos principais fatores responsáveis por altas taxas de interrupção do tratamento.…”
Section: Antipsicóticos Atípicosunclassified